Studi Kasus Perilaku Merokok sebelum dan Saat Pandemi Covid-19 Kelurahan Cicaheum Kota Bandung Tahun 2022 - Ruhyat, Ejeb; Audia, Salma Syifa (LPPM Hang Tuah Pekanbaru, 2025)
The Ministry of Health reports that smokers will have a greater chance of getting COVID-19 in 2020 compared to non-smokers. This study aims to do two things:(1) determine if smoking habits changed before and during the COVID-19 pandemic, and(2) learn about the causes and effects of people's smoking habits during the epidemic. This study used a mixed-methods explanatory sequential design as its research technique. Before moving on to qualitative research, the study employs quantitative approaches. Directly distributed questionnaires were used to collect quantitative data. Qualitative information was derived from extensive interviews and careful observation. The data showed that smoking locations did not vary before or during the pandemic (p = 0.679). The amount of time spent smoking did not change (p=0.570). Before and during the epidemic, there were various kinds of cigarettes (p=0.008). Cigarette smoking rates were lower before the COVID-19 epidemic and higher after it ended (p=0.030). Because of the pandemic's lack of physical activity and the fact that informants do not experience the health hazards of smoking, they continue to smoke. Smoking has a favorable impact on informants' well-being, leading to feelings of relaxation, comfort, and decreased burdens; it also has an economic impact, since expenditure on smoking is greater than other costs. Recommendation for smokers to cut down on cigarette usage to lower smoking risks.